Preserving Sunken Military Vessels as Underwater Cultural Heritage in Colombia: Legal Challenges and Prospects for the USS Kearsarge Wreck Site - William Gomez Pretel; Moonsoo Jeong; Camilo Ernesto Rodríguez-Gutiérrez; Agustin Ortiz JR (Heritage, 2023)
This study examines the legal challenges related to preserving sunken military vessels as Underwater Cultural Heritage (UCH) in Colombia. These challenges include Spanish galleon shipwrecks, limited international cooperation, and the lack of legal recognition for sunken military vessels under domestic law (Law 1675 of 2013). To address these issues, this article reviews the concepts of warship and sovereign immunity as they relate to the status of sunken military vessels. The study places a particular focus on the USS Kearsarge, a military shipwreck in Colombian territorial waters protected by the Sunken Military Craft Act of 2004 (SMCA) of the United States. Additionally, it analyzes the legal frameworks and management of UCH in both Colombia and the United States, as well as providing two lists of Colombia’s sunken military vessels and foreign sunken military vessels in its waters. The research concludes by highlighting the complexities of managing UCH in Colombia and offering a prospectus on the future of the USS Kearsarge wreck site as shared heritage. Ultimately, this study underscores the need for a more comprehensive legal framework and greater international cooperation to ensure the preservation and protection of sunken military vessels in Colombia.